Implementasi Bermain Model “ASYIK” Untuk Meningkatkan Semangat Belajar Anak Melalui Kegiatan Outbound Di TK Aisyiyah Bustanul Athfal 46 Daun - Susy Humayrah; Sri Watini (LP. Ma'arif Janggan Magetan, 2022)
Early childhood education should not only be academically oriented, but should be able to provide new learning experiences for children. Therefore, teachers are required to be more creative and innovative in creating learning methods that are considered to be able to increase the enthusiasm and enthusiasm of students, namely through outbound activities. In addition to increasing children's enthusiasm for learning, outbound can also develop children's self-confidence, talents, and potential. This study aims to increase children's enthusiasm for learning through